In vitro characterization of Acrocomia totai defatted kernel meal as a novel raw material in Nile tilapia Oreochromis niloticus feed and the effect of exogenous phytase inclusion over nitrogen and phosphorus bioavailability - Casaretto, Matías Ezequiel; Travaini, Franco Luciano; Wassner, Diego Fernán; Pazos, Adriana Alejandra; Azcuy, Rosendo Lucas (2021)
This work aimed to explore the potential value of the Acrocomia totai defatted kernel meal as an alternative feed ingredient for Nile tilapia (Oreochromis niloticus) diet. In vitro assays were conducted simulating tilapia digestion. Soybean meal was included as a reference and two phytase doses were assayed. After running the gastrointestinal simulations, amino acids bioavailability from soybean meal with phytase addition was higher than in the other treatments. However, when expressed on a crude protein content basis, the relative performance of the treatments with A. totai improved. The protein composition of the raw materials affected their performance because of globulins and specific amino acids such as arginine, lysine and histidine. A higher relative contribution of these last in Acrocomia kernel protein determined their lower compared performance. Phosphorus bioavailability from Acrocomia, expressed on a dry matter basis, was the highest, but increments resulting from phytase addition, expressed on a phytic acid basis, were not significantly different between raw materials. Therefore, no specific affinity between phytase and the raw materials’ phytic acid was evidenced. This study demonstrated that A. totai kernel meal has potential as a protein source in aquafeed but also it has limitations: it is a big phytic phosphorus source that is only available with phytase addition.